CLAUSA restricts tomato leaf morphogenesis and GOBLET expression. (25th August 2015) - Bar, Maya; Ben‐Herzel, Ori; Kohay, Hagay; Shtein, Ilana; Ori, Naomi
Summary: Leaf morphogenesis and differentiation are highly flexible processes. The development of compound leaves is characterized by an extended morphogenesis stage compared with that of simple leaves. The tomato mutant clausa ( clau ) possesses extremely elaborate compound leaves. Here we show that this elaboration is generated by further extension of the morphogenetic window, partly via the activity of ectopic meristems present on clau leaves. Further, we propose that CLAU might negatively affect expression of the NAM/CUC gene GOBLET ( GOB ), an important modulator of compound‐leaf development, as GOB expression is elevated in clau mutants and reducing GOB expression suppresses the clau phenotype. Expression of GOB is also elevated in the compound leaf mutant lyrate ( lyr ), and the remarkable enhancement of the clau phenotype by lyr suggests that clau and lyr affect leaf development and GOB in different pathways. Significance Statement: Tomato leaves are remarkably varied in size and form. Here, characterization of the tomato mutant clausa ( clau ) uncovered additional morphogenetic potential of the tomato leaf. We propose that CLAU negatively affects the expression of the NAM/CUC gene GOBLET ( GOB ), a known modulator of compound leaf development.